Clinicopathological Study of Thyroid Swelling with High Resolution Ultrasonographic Correlation - Kumar Gaurav; Rajeev Kumar Ranjan; Gunjan; Zahid Mustafa Khan; Anima R. Xalxo; Nisha Rai (Journal of Pharmacy and Bioallied Sciences)
Background: Epidemiological data show a high frequency of thyroid nodules in the general population, with rates increasing with age. Aim and Objectives: To analyze thyroid swelling with high-resolution ultrasonographic correlation. Results: 90% of cases were surgically treated. Surgical decision made on basis of age, gender of patient, size of thyroid mass, thyroid profile FNAC, ultrasonographic reports, and other patient related factor. Conclusion: The findings provide a thorough understanding of thyroid pathology, paving the door for more effective diagnostic approaches and personalized therapeutic strategies in clinical practice.